Respuesta :

Answer:

[tex]$g=\frac{2 -3f}{f}, f\neq 0$[/tex]

Step-by-step explanation:

[tex]fg + 2f - g = 2 - (f + g)[/tex]

[tex]fg + 2f - g = 2 - f - g[/tex]

Add [tex]g[/tex] to both sides

[tex]fg + 2f = 2 - f[/tex]

Add [tex]-2f[/tex] both sides

[tex]fg + 2f-2f = 2 - f -2f[/tex]

[tex]fg = 2 -3f[/tex]

Divide both sides by [tex]f[/tex]

[tex]$\frac{fg}{f} = \frac{2 -3f}{f} $[/tex]

[tex]$g=\frac{2 -3f}{f}$[/tex]

But [tex]f[/tex] can't be zero because it is undefined. So,

[tex]$g=\frac{2 -3f}{f}, f\neq 0$[/tex]